Analisis Kebijakan Publik Restorative Justice dalam Kasus Narkotika di Polresta Gorontalo Kota - Putri Djaura Rivai; Rusli Isa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Restorative justice implementation in drug abuse cases at Polresta Gorontalo Kota faces complex institutional challenges. Although this approach offers a more humane pathway for drug users’ recovery, it has not yet been systematically integrated into law-enforcement governance. This study examines the dynamics of restorative justice implementation, identifies structural barriers, and formulates adaptive governance strategies. Employing a descriptive qualitative approach, data were collected through interviews, observation, and document analysis. Findings show that most drug cases involve users with small amounts of evidence, yet only a small proportion are diverted to restorative pathways. Key obstacles include limited understanding among officers, the absence of specific standard operating procedures (SOPs), and weak coordination between units. The discussion emphasizes the need for institutional reform through targeted training, the establishment of coordination forums, and the development of locally based operational procedures. The study concludes that restorative justice holds substantial potential for effective application in drug cases, provided it is supported by planned governance reforms and strong institutional commitment.